Associations of procalcitonin, C‐reaction protein and neutrophil‐to‐lymphocyte ratio with mortality in hospitalized COVID‐19 patients in China (2020)
Coronavirus disease 2019 (COVID-19) is an important and urgent threat to global health. Infammation factors are important for COVID-19 mortality, and we aim to explore whether the baseline levels of procalcitonin (PCT), C-reaction protein (CRP) and neutrophil-to-lymphocyte ratio (NLR) are associated with an increased risk of mortality in patients with COVID-19. A retrospective study was conducted and a total of 76 patients with confrmed COVID-19 were included between January 17, 2020 to March 2, 2020, of these cases, 17 patients were dead. After adjusting covariates, PCT (≥ 0.10 ng/ mL) and CRP (≥ 52.14 mg/L) exhibited independent increasing risks of mortality were used hazard ratio (HR) of 52.68 (95% confdence interval [CI]: 1.77–1571.66) and 5.47 (95% CI: 1.04–28.72), respectively. However, NRL (≥ 3.59) was not found to be an independent risk factor for death in our study. Furthermore, the elevated PCT levels were still associated with increasing risk of mortality in the old age group (age≥ 60 y), and in the critically severe and severe patients after adjustment for complications. Thu Baseline levels of PCT and CRP have been addressed as independent predictors of mortality in patients with COVID-19.